On the Effect of Combination of Statistical and Judgemental Stock Control Methods - Inna Kholidasari (Jurnal Teknik Industri, 2014)
Stock control is the most important aspect in an inventory system. It determines the safety stock in order to ensure that products are readily available when the customers require them. The decision makers in organizations tend to rely on software solution in obtaining stock control solutions since they have to manage a massive number of Stock Keeping Units (SKUs). However, managers intervene in the system and use their judgement to adjust or decide on various quantitative elements. This research discusses the effects of combination of stock control methods. An extended database of approximately 1,800 SKUs from an electronics company is analyzed. Then, a simulation experiment is performed in order to evaluate in a dynamic fashion what are the effects of applying combined stock control methods. The findings indicate that the combined method of stock control seems to improve the performance of the inventory system, especially in reducing inventory investment.